2022
DOI: 10.1063/5.0102078
|View full text |Cite
|
Sign up to set email alerts
|

The effect of relative air humidity on the evaporation timescales of a human sneeze

Abstract: The present paper investigates droplet and aerosol emission from the human respiratory function by numerical and experimental methods, which is analyzed at the worst-case scenario, a violent sneeze without a face covering. The research findings develop the understanding of airborne disease transmission relevant to COVID-19, its recent variants, and other airborne pathogens. A human sneeze is studied using a multiphase Computational Fluid Dynamics (CFD) model using detached eddy simulation coupled to the emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…(6) and vapor transport Eq. (7) included the energy source term S e,evap, and vapor concentration source term S Y,evap from droplet evaporation ( Fontes et al, 2020 ; Stiehl et al, 2022 ). Therefore, they included the influences of droplets' evaporation on changing the local humidity and temperature.…”
Section: Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…(6) and vapor transport Eq. (7) included the energy source term S e,evap, and vapor concentration source term S Y,evap from droplet evaporation ( Fontes et al, 2020 ; Stiehl et al, 2022 ). Therefore, they included the influences of droplets' evaporation on changing the local humidity and temperature.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Understanding the dynamic behavior of respiratory droplets under different indoor conditions can suggest prevention guidelines to reduce COVID-19 spread ( Wang et al, 2021 ). Previous studies introduced various techniques for measuring the respiratory droplet velocity profiles, including particle image velocimetry (PIV) and laser Doppler anemometry ( Bahl et al, 2020 ; Stiehl et al, 2022 ), and airflow visualization methods such as shadowgraph imaging (Tang et al, 2013). However, due to the limitations of experiments in determining short-range/direct transmission of respiratory droplets, computational fluid dynamics (CFD) modeling was also used in the literature ( Vuorinen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 6, instead, the role of ambient relative humidity on the evaporation of droplet from a sneeze is analyzed. The effectiveness of face masks in absorbing the larger droplets and limiting the diffusion of smaller droplets is assessed numerically in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the exhaled microorganisms could also travel 2 m and remain suspended in the air within a room. Stiehl et al (2022) used the particle imaging velocimetry (PIV) to studies the evolution of aerosols and droplets expelled during a human sneeze. They extracted the sneeze emission concentration at 0.6 m and 0.9 m away from the mouth and found that maximal concentration is found in region slightly lower than the mouth at 0.6 m. These studies shed light on the droplets and aerosols transmission and reveal the influencing factors.…”
Section: Introductionmentioning
confidence: 99%